The liberalization of public services and their impact of on the competitiveness of firms: a case study in the Alpine regions of Switzerland - Christof Abegg; Alain Thierstein (European Regional Science Association (ERSA), 2003)
In the wake of a general process of economic transformation public services in recent years have undergone a number of radical changes. Under the key word of ?liberalization? the markets of public services in Europe have been opened up to market competition. Questions of efficiency and productivity in the provision are gaining significance. But the liberalization cannot only be analysed through a one-dimensional economic lense. Therefore, the goal of our paper is to clarify the spatial impact of these liberalization trends. We focus on four public services: regional public transport, postal services, telecommunications and electricity. In the first part we will lay the conceptual basis for a differentiated consideration of the spatial effects of the liberalization of public services. We hypothesize that the liberalization of the public services has given rise to spatial differentiation in the provision of these public services, which in turn reduces the competitiveness of companies in the peripheral and mountain regions. Thus, it is a typology of the functions of public services that will help to sharpen the view on the various ongoing changes. To analyse the impact on the competitiveness of firms the paper will look at the relative significance of the following aspects of public services: locational factors; direct and indirect effects on the production process; companies' ability to adapt to external changes. The main analytical approach to assess firms behaviour within a regional context is the concept of ?regional innovation and production systems' (RIPS). RIPS are characterised by their scope for autonomous decision-making, their coordination mechanisms and their specific resources. The extent to which they are anchored in their particular region influences their capacity for innovation and adaptation to a changing economic context. The second part of the paper presents some first results from an ongoing empirical study in the Alpine Regions of Switzerland, using data from a written firm survey. The third section draws first conclusions regarding the relative spatial impacts of the liberalisation processes. The paper finishes off with some preliminary implications on political strategies for guaranteeing sufficient provision of public services to peripheral and mountain regions.
Keywords: 330